Coping Strategies Among Brazilian Pregnant Women Living With HIV - Faria, Evelise Rigoni de; Gonçalves, Tonantzin Ribeiro; Carvalho, Fernanda Torres de; Lopes, Rita de Cássia Sobreira; Piccinini, Cesar Augusto (Paidéia (Ribeirão Preto), 2014)
Pregnant women living with HIV (PWLH) face tremendous challenges in order to prevent their babies’ infection. Coping is a potential buffer against negative outcomes from these challenges. This study aims to describe coping strategies of PWLH. This cross-sectional survey involved 77 PWLH from a public health care center in Brazil. Coping was measured for three types of strategies: Problem-focused, Emotion-focused, and Relationship support. Multivariate analyses identified some coping predictors. Being employed, reporting religious practice and higher CD4/immunity were associated with Problem-focused coping. Lower educational level was associated with Emotion-focused strategies. Relationship support strategies were more likely to be reported by PWLH who had good social support, who had disclosed HIV status to the baby’s father, and who knew their infection before pregnancy. Findings underline the need for HIV interventions focused on social support and participation by the baby’s father, with particular attention to those PWLH who were recently diagnosed and economically vulnerable.